2012
DOI: 10.1146/annurev-polisci-031710-103823
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Accountability: Recent Theoretical and Empirical Work

Abstract: Competitive elections create a relationship of formal accountability between policy makers and citizens. Recent theoretical work suggests that there are limits on how well this formal accountability links policy decisions to citizen preferences. In particular, incumbents' incentives are driven not by the voters' evaluation of the normative desirability of outcomes but by the outcome's information about the incumbent's type (e.g., competence or ideology). This review surveys both this body of theory and the rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(229 citation statements)
references
References 55 publications
5
221
0
3
Order By: Relevance
“…After all, by the time of the campaign, voters had already learned about the incumbent from his performance in office. This suggests that See recent articles by Dewan and Shepsle (2011) and Ashworth (2012) for a review of the agency and spatial modeling approach to elections. voters learn using role-specific technologies.…”
Section: Introductionmentioning
confidence: 99%
“…After all, by the time of the campaign, voters had already learned about the incumbent from his performance in office. This suggests that See recent articles by Dewan and Shepsle (2011) and Ashworth (2012) for a review of the agency and spatial modeling approach to elections. voters learn using role-specific technologies.…”
Section: Introductionmentioning
confidence: 99%
“…We thus focus on prospective economic voting, where the selection motive for evaluating government competence is particularly sensitive to variation in the quality of performance signals (Ashworth 2012;Fearon 1999). …”
mentioning
confidence: 99%
“…Furthermore, we borrow from the political agency literature with adverse selection. The latter studies how the voter updates her beliefs about the politicians' type after having observed their performance in office (Ashworth, 2012;Banks andSundaram, 1993, 1996;Besley, 2006;Fearon, 1999;Persson and Tabellini, 2000, and others). The fourth strand of related literature combines political competition between policy-motivated citizen-candidates with electoral accountability and analyzes the trade-offs thereof (Bernhardt et al, 2011;Van Weelden, 2013, 2015.…”
Section: Related Literaturementioning
confidence: 99%